1995
DOI: 10.1016/0376-7388(95)00014-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and theory of gas transport in microporous sol-gel derived ceramic membranes

Abstract: Sol-gel modification of mesoporous alumina membranes is a very successful technique to improve gas separation performance. Due to the formed microporous top layer, the membranes show activated transport and molecular sieve-like separation factors. This paper concentrates on the mechanism of activated transport (also often referred to as micropore diffusion or molecular sieving). Based on a theoretical analysis, results from permeation and separation experiments with H2, CO2, 02, N2, CH4 and iso-CaHlo on microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
133
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(140 citation statements)
references
References 29 publications
3
133
2
2
Order By: Relevance
“…Table 1 lists the activation energies calculated from Figure 5, together with some data on pure and metal-oxide-doped silica membranes that have been reported elsewhere. [20][21][22][23][24][25][26] The values measured in the present study are close to those reported by Nair et al, who found activation energies for helium permeance of 23 kJ mol À1 in silica. [21] Asaeda and co-workers reported an increase in apparent activation energy of H 2 permeance from 3.4 to 44 kJ mol À1 when the Zr dopant loading in silica was increased from 10 mol % to 90 mol %.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Table 1 lists the activation energies calculated from Figure 5, together with some data on pure and metal-oxide-doped silica membranes that have been reported elsewhere. [20][21][22][23][24][25][26] The values measured in the present study are close to those reported by Nair et al, who found activation energies for helium permeance of 23 kJ mol À1 in silica. [21] Asaeda and co-workers reported an increase in apparent activation energy of H 2 permeance from 3.4 to 44 kJ mol À1 when the Zr dopant loading in silica was increased from 10 mol % to 90 mol %.…”
supporting
confidence: 91%
“…Such a highly negative value suggests a high enthalpy of sorption. The literature values in Table 1 indicate either positive activation energies for CO 2 permeance [22,23] or slightly negative values. [20] Apart from data in a study in which activation energies of À9.2 to À11.2 kJ mol À1 were measured, [24] none of the reported values is close to (À14.2 AE 0.6) kJ mol À1 as measured on the NS membrane.…”
mentioning
confidence: 99%
“…After the addition was completed, the reaction mixture was heated to 60 • C for 3 h under constant stirring in a glove box. The standard silica sol molar TEOS:HNO 3 :H 2 O:EtOH ratio was 1:0.085:6.4:3.8 [13,14].…”
Section: Sol Preparationmentioning
confidence: 99%
“…In contrast to sp5-220 nm and sp10-220 nm membranes, the N 2 and O 2 permeances through sp10-220 nm membrane consolidated from ethylene glycol diluted sol increased up to 350 K and stayed constant up to 400 K but the CO 2 permeance remained almost constant with increasing temperature. The increase in permeance values with increasing temperature leads to positive activation energy indicative of activated transport mechanism through the microporous selective layer [14,25]. The positive activation energy might be caused by either the formation of organically bound species due to utilizing ethylene glycol as a dilution medium that prevents the formation of microcracks on membrane surface or lower drying stress caused by slow drying in the course of ethylene glycol evaporation that might result in microcrack free membrane surface.…”
Section: Gas Permeationmentioning
confidence: 99%
See 1 more Smart Citation